Penggunaan Media Pembelajaran Fisika dengan Virtual Laboratory Berbasis "PhET Interactive Simulations" pada Peserta Didik Kelas XII IPA 3 MAN 1 Sleman Tahun Ajaran 2022/2023. - Musahir Musahir (Madaris: Jurnal Guru Inovatif, 2024)
The research conducted is the utilization of physics learning media with Virtual Laboratory based on "PhET Interactive Simulations" by physics teachers as an effort to improve students' mastery of the Resistor Circuit physics material based on the average values obtained by students of class XII MAN 1 Sleman. This study aims to determine the improvement of mastery of the Electric Circuit material using "PhET Interactive Simulations". This descriptive study used a one-group pre-test and post-test design with a sample of class XII IPA 3 selected randomly. From a population of 36 students, a sample of 33 students was taken. The instruments used were test and non-test instruments. The test instrument consisted of pre-test and post-test, while the non-test instrument was in the form of worksheets filled out after the learning process. The results showed that in the pre-test, 90.9% of students were classified as failing and 9.1% were classified as sufficient with an average achievement score of 66.27. The results of the analysis of the cognitive aspect of mastery of the Resistor Circuit concept during the learning process using "PhET Interactive Simulations" showed that the average achievement score of students was 37.3% in the very good category and 56.5% in the good category. These results were obtained from the completion of questions in the worksheets. The students' abilities after the learning process showed a change, with the average achievement score of the post-test reaching 90.06, which is classified as good. The results of the N-Gain test obtained a score of 0.70, which is categorized as high. It can be concluded that there is an improvement in mastery of the Resistor Circuit material after using the Virtual Laboratory based on "PhET Interactive Simulations.